Particle Image Velocimetry Dynamic Analysis on the Penstock Vortex Flow for the Dam Reliability Study - Zahari N.M.; Zawawi M.H.; Ng F.C.; Sidek L.M.; Abas A.; Nurhikmah F.; Aziz N.A.; Hao T.L.; Radzi M.R.M. (Springer Science and Business Media Deutschland GmbH, 2023)
Flow visualization; Reliability analysis; Velocimeters; Vortex flow; Downs model; Dynamics analysis; Flow visualisation; Numerical simulated; Operating configurations; Particle image velocimetry analysis; Physical modelling; Velocity measurement